2021
DOI: 10.1097/01.asw.0000755844.87283.20
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Skin Failure: A Scoping Review

Abstract: OBJECTIVE To map the use of the term “skin failure” in the literature over time and enhance understanding of this term as it is used in clinical practice. DATA SOURCES The databases searched for published literature included PubMed, Embase, the Cumulative Index for Nursing and Allied Health Literature, and Google Scholar. The search for unpublished literature encompassed two databases, Open Gray and ProQuest Dissertation and Theses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 130 publications
(227 reference statements)
0
9
0
Order By: Relevance
“…13 A recent scoping review was done to map the use of the term skin failure in hopes of enhancing understanding of how it is used in clinical practice. 24 The authors identified 180 articles that met the inclusion criteria focused on identifying and synthesizing literature on unavoidable skin injuries appearing at end of life. Four themes were identified: (1) four names for the same problem, namely, skin failure, SCALE, KTU, and Trombley-Brennan; (2) knowledge gaps exist on the pathophysiology of the KTU as it currently is based on hypotheses; (3) differences exist between the KTU and the other injuries; and (4) gaps also exist in care approaches.…”
Section: Skin Failure Then and Now: A Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…13 A recent scoping review was done to map the use of the term skin failure in hopes of enhancing understanding of how it is used in clinical practice. 24 The authors identified 180 articles that met the inclusion criteria focused on identifying and synthesizing literature on unavoidable skin injuries appearing at end of life. Four themes were identified: (1) four names for the same problem, namely, skin failure, SCALE, KTU, and Trombley-Brennan; (2) knowledge gaps exist on the pathophysiology of the KTU as it currently is based on hypotheses; (3) differences exist between the KTU and the other injuries; and (4) gaps also exist in care approaches.…”
Section: Skin Failure Then and Now: A Historical Perspectivementioning
confidence: 99%
“…Four themes were identified: (1) four names for the same problem, namely, skin failure, SCALE, KTU, and Trombley-Brennan; (2) knowledge gaps exist on the pathophysiology of the KTU as it currently is based on hypotheses; (3) differences exist between the KTU and the other injuries; and (4) gaps also exist in care approaches. 24 Another scoping review conducted in 2019 identified that knowledge on the KTU is limited, no validated assessment tool is available, and the KTU may be misclassified as a PI. 25 One assessment scale was reported in the literature based on a retrospective study of 52 acute care patients who experienced ASF prior to death.…”
Section: Skin Failure Then and Now: A Historical Perspectivementioning
confidence: 99%
“…11 This condition has several names, including Kennedy terminal ulcers, skin changes at life's end, and Trombly-Brennan terminal tissue injuries. 12 Furthermore, reports in the literature suggest skin failure may occur on a spectrum that includes acute, chronic, and end-of-life skin. 11 Acute skin failure appears during a critical illness such as shock.…”
Section: Skin Failurementioning
confidence: 99%
“…Initial stages of skin failure may present as mottling, blisters, ulceration, and even gangrene. 12 Skin failure should be considered if skin damage appears suddenly and rapidly deteriorates to necrosis or full-thickness tissue loss. 13 Patients with skin failure may be misdiagnosed as having a deep tissue injury, or unstageable or full-thickness pressure ulcer or injury.…”
Section: Diagnosismentioning
confidence: 99%
“…Some attempts have been made to define "skin failure" with two distinct and quite different meanings, which reflect, in a way, an "inside out" vs an "outside in" pathogenetic process. [1][2][3][4][5] On one hand, the term has been used, mainly in the "wound care" area, to refer to regional or localized loss of substance, such as pressure ulcers, especially in critically ill patients. [6][7][8][9][10] Skin failure, in this meaning, is defined as "an event in which the skin and underlying tissue die due to hypo-perfusion that occurs in concomitance with failure of other organs," especially in the context of a Multi-Organ Dysfunction Syndrome (MODS), or as part of the dying process at the end of life (Skin Changes at Life's End, 'SCALE').…”
mentioning
confidence: 99%